THE MISTAKEN PRONUNCIATIONS: THE UNAVAILABILITY OF SOME ENGLISH CONSONANTS IN BAHASA - Jaya, Made Suardika (Yavana Bhasha : Journal of English Language Education, 2019)
This paper aims at showing the problems with reference to pronunciation of English sentences spoken by Indonesians. The unavailability of some English consonants in Bahasa could lead the Indonesians into mistaken pronunciations. To obtain the data of how well the English pronunciations uttered by the Indonesians, a speaking test was held. The respondents for this test are fifteen Indonesians with different ages and social backgrounds. The results show that the English consonants which are absent in Bahasa caused some puzzlement for the speakers which made them had a tendency to pronounce the words by using the nearest sound from the Bahasa phonemes towards the English phonemes. Fine comprehension by reading English dictionary frequently together with adequate proper listening and speaking practises are needed by the non native speakers in order to achieve better ability related to English pronunciation.Â